Study on the reaction mechanism and kinetics of limestone hydrogenation by micro fluidized bed: Effect of H2 concentration and natural limestone - Hengrui Jin; Haiping Yang; Xianhua Wang; Yang Yang; Yingquan Chen (Carbon Capture Science & Technology)
Limestone decomposition is the first step in cement production, which produces a significant amount of CO2 and poses a significant challenge to achieve carbon neutrality. Hydrogenation of limestone can produce CO or CH4 instead of CO2, which can be considered as a new way of carbon capture, making it a promising method for carbon emission reduction. In this work, pure CaCO3 and several natural limestone samples were hydrolyzed under varying H2 concentration using a micro fluidized bed (MFB) reactor combined with online mass spectrometry to reveal the mechanism and kinetics of limestone hydrogenation.The main gases produced by hydrogenation at 1 atm are CO and CO2. The CO2 comes from the calcination of CaCO3. The CO comes from 2 steps: the first step is the in-situ hydrogenation of CaCO3 and the second step is the Reverse Water Gas Shift (RWGS) reaction. The activation energy (Ea) of CO2 formation in H2 atmosphere is lower than in Ar atmosphere. However, there is no obvious effect of different H2 concentrations on the Ea of CO2 formation. The Ea of CO in situ formation is 72.70 KJ/mol, 54.53 KJ/mol, 71.34 KJ/mol and 60.29 KJ/mol in 10%, 30%, 50% and 70% H2 atmosphere, respectively. The H2 concentration also has no significant effect on the in-situ CO evolution. However, the H2 concentration can affect the Ea of CO produced by RWGS. The Ea is 75.67 KJ/mol, 167.59 KJ/mol and 221.47 KJ/mol in 10%, 30% and 50% H2 atmosphere, and this reaction doesn't occur in 70% H2 atmosphere. Compared with the pure CaCO3, the hydrogenation of limestone can produce more CO and less CO2. In limestone, impurity elements are the main factor affecting the reaction kinetics. Transition metals can increase the rate of CO2 production, but have no apparent effect on CO. The CO2 yield of high impurity limestone is higher than that of limestone with low impurities. Transition metals can also reduce the Ea of CO2 formation and the RWGS reaction. In the 50% H2 atmosphere, the Ea of CO2 formation is 88.87 KJ/mol and the Ea of CO from RWGS is 137.60 KJ/mol. However, under the same conditions, the Ea of pure CaCO3 is 126.91 KJ/mol and 221.47 KJ/mol.